Spiritual-Intellectual Balance in Al-Ghazali’s Educational Epistemology: Toward a Framework for Modern Islamic Education - Misbahul Arifin; Ahmad Rifa’i; Rezki Nila Munanna; Fazarina Nurfatihah (Journal of Islamic Education and Learning, 2026)
This study focuses on Al-Ghazali’s thought regarding the spiritual-intellectual balance in the epistemology of Islamic education, aiming to reveal its relevance and contribution to contemporary educational challenges. Employing a qualitative method with a library research approach, primary data were obtained from Ihya’ ‘Ulum al-Din, while secondary data were drawn from contemporary articles and scholarly journals. Data were analyzed using content analysis and philosophical hermeneutics to interpret the educational concepts in Al-Ghazali’s perspective. The findings indicate that Al-Ghazali emphasizes the integration of knowledge, practice, the heart, and ethics as a holistic framework of educational epistemology. These results demonstrate that the spiritual-intellectual balance is essential for building an educational system that not only develops intellectual capacity but also strengthens the moral and spiritual character of learners. The implication of this research highlights the importance of integrating classical epistemology into modern educational practice to establish a more comprehensive and relevant paradigm of Islamic education.